A two-step model for the tunneling conductivity of polymer carbon nanotube nanocomposites assuming the conduction of interphase regions. Issue 79 (27th October 2017) - Razavi, Razieh; Zare, Yasser; Rhee, Kyong Yop
Abstract : This work develops a two-step model for the conductivity of polymer carbon nanotube (CNT) nanocomposites (PCNT) assuming the properties of tunneling and interphase regions. Abstract : This work develops a two-step model for the conductivity of polymer carbon nanotube (CNT) nanocomposites (PCNT) assuming the properties of tunneling and interphase regions. In step 1, CNT and the surrounding interphase are considered as pseudoparticles and a simple model predicts their conductivity. After that, a suitable model calculates the conductivity of nanocomposites containing pseudoparticles, tunneling regions and polymer matrixes in step 2. The waviness of CNT as well as the fractions of CNT and interphase regions in the conductive networks is also considered. The experimental results of several samples and the reasonable roles of all parameters in the conductivity of nanocomposites support the predictions of the two-step model. Thin and long CNTs can cause a high conductivity, but only thick CNTs result in the least conductivity. Also, the thickness and conduction of interphase zones directly control the conductivity of nanocomposites. So, it is important to provide a strong interphase in PCNT to achieve a high conductivity. Moreover, a poor percolation threshold and a short tunneling distance enhance the conductivity of nanocomposites, whereas only a large tunneling distance dominantly reduces the conductivity.